2016
DOI: 10.1007/s12078-016-9206-2
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Retronasal Odor Responsiveness: Effects of Aging and Concurrent Taste

Abstract: Introduction Individual differences in taste sensitivity have been considered the primary chemosensory factor in studies of chemical senses/ingestive behavior. Recent findings suggest, however, that retronasal odor perception is equally important in food preference and selection and, furthermore, the presence of a congruent taste can modulate responsiveness to retronasally perceived odors. The primary objective of this study was to measure individual differences in responsiveness to food odors in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Olfactory detection thresholds are a known source of variation. Although they are usually reported as a single value (group best estimate threshold), they commonly vary between individuals by 3 orders of magnitude or more and typically 14–23% of individuals are insensitive to a given odor . Other plausible factors that might contribute to interindividual variation in flavor perception from glycosides include variations in the saliva flow rate and buffering capacity and mouth movement and breathing behavior …”
Section: Introductionmentioning
confidence: 99%
“…Olfactory detection thresholds are a known source of variation. Although they are usually reported as a single value (group best estimate threshold), they commonly vary between individuals by 3 orders of magnitude or more and typically 14–23% of individuals are insensitive to a given odor . Other plausible factors that might contribute to interindividual variation in flavor perception from glycosides include variations in the saliva flow rate and buffering capacity and mouth movement and breathing behavior …”
Section: Introductionmentioning
confidence: 99%
“…However, flavor depends more on oral presentation, a key component of which is retronasal olfaction (Delwiche 2004;Shepherd 2006). Since nasal concentration, patterns of sorption on the nasal mucosa, and neural processing can differ between routes of presentation, sensation may also differ (Linforth et al 2002;Bojanowski and Hummel 2012;Scott et al 2014;Flaherty and Lim 2017;Hannum et al 2018;Blankenship et al 2019;Sanganahalli et al 2020). Accordingly, one goal was to measure oral sensitivity to 3 M solutions, including detection thresholds (Experiment 1), recognition thresholds (Experiment 2), and supra-threshold intensity vs. concentration (Experiment 3).…”
Section: Human Oral Sensitivity To 3 Mmentioning
confidence: 99%
“…The variability in human umami taste perception is still poorly understood, however a genetic mechanism is possibly behind these variations, with links to the heterodimeric receptor T1R1 and T1R3 (Raliou et al 2009;. Different studies conducted a comprehensive evaluation of single-nucleotide polymorphisms (SNPs) and haplotypes in human TAS1R1 and TAS1R3 genes and revealed several SNPs within the extracellular domain of T1R1 and T1R3 (Chen et al 2009;Flaherty and Lim 2017;Puputti et al 2018;Satoh-Kuriwada et al 2014;Simmons and Estes 2008;Singh, Schuster, and Seo 2010). Raliou et al (2009) found variations in genes T1ASR1 and TAS1R3 in human fungiform papillae and suggested that these receptor variations contributed to the individual differences in glutamate sensitivity in the studied population (European Caucasian) (Raliou et al 2009).…”
Section: Individual Differences To Umami Perceptionmentioning
confidence: 99%